Driving the Twin Bore Running Tunnels by Earth Pressure Balance Machine on the Sound Transit C-710 Beacon Hill Station and Tunnels Project - Steve Redmond; Chris Tattersall; Nestor Garavelli; Tomyuki Kudo; Peter Raleigh; Michael J. Lehnen (Society for Mining, Metallurgy & Exploration, 2007)
Twin bore running tunnels driven approximately 4,500 route feet by a Mitsubishi Heavy Industries (MHI) EPB Tunnel Boring Machine link the West Portal and East Portal on this complex Light Rail Project. One third along the way, the TBM arrives at the Beacon Hill Station which is the deepest underground “binocular” station of its kind in North America and then “walks-across” the station to be re-launched on the other side to complete the drive. This paper discusses briefly the layout and design considerations but then focuses more deeply on the approach by the Contractor to drive and supply the tunnel. The paper addresses the approach used to launch, re-launch and recover the TBM and touches briefly on muck volume control and monitoring plus settlement monitoring and the performance achieved. Also of interest is a unique solution to a difficult launch situation involving a secant pile tieback wall designed with several rows of double I-beam steel walers spanning the eye at the West Portal under the I-5 freeway.